Relationship between Digital Stress and Career Stress Levels of Sports Science Students - Ahmet Dinç; Abdullah Altunhan; Ünsal Tazegül (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In recent years, there has been a marked increase in the use of the internet and internet-based systems. This study aims to explore the relationship between digital stress and career stress among students in the Faculty of Sports Sciences at Iğdır University. A survey model was employed, with the research population comprising students from the Faculty of Sports Sciences at Iğdır University. The sample included 446 voluntary participants (270 female and 176 male). Statistical analyses were conducted using the SPSS 25.0 software, employing both descriptive statistics and Pearson correlation analysis. The findings indicate that both digital stress and career stress scores among sports science students were above average. Furthermore, a highly significant positive correlation was found between digital stress and career stress levels.